Belarus and COVID-19: the experience of sociological research - Kudrevich, Maxim A.; Sakharava, Katsiaryna V.; Shkurova, Alena V. (Journal of the Belarusian State University. Sociology, 2023)
The spread of coronavirus infection in 2020 necessitated the development of new forms of behaviour and norms for their regulation. The experience of a sociological study of ways of adapting the population to the spread of COVID-19, based on the popularisation of protective and restrictive anti-COVID practices, is analysed. Protective practices include washing hands, using antiseptic and wearing medical masks in public places, while restrictive practices include localising communication and avoiding public places. The features of the dynamics of self-preserving and health-saving behaviour as one of the necessary measures of reproduction and security of the individual are studied. Prospects for the transformation of anti-COVID practices are characterised. Their specificity is manifested in the fact that, despite the rapid spread of infection, without the impact of a risk factor, they lose their relevance. The attitude of the population to vaccination, as well as its features, is considered. They consist in the fact that the population ceases to perceive COVID-19 as a serious threat, treats preventive measures as a recommended, not a mandatory norm. The assessment by the population of the success of the Belarusian experience in combating coronavirus infection and the effectiveness of the Belarusian healthcare system, as well as the prospects for changing the perception of coronavirus infection, is presented. They are associated with the gradual getting used to the pandemic reality, which often carries the threat of ignoring the problems and dangers associated with the spread of COVID-19.